Topological phases driven by orbital entanglement in Transition Metal Oxide Perovskite interfaces - Gabay, Marc (Comptes Rendus. Physique)
The deceptively simple crystallographic structure of early transition metal oxide perovskites belies the complexity and variety of electronic, magnetic and structural phases that they display. Structural defects, rotations, tilts, deformations of the oxygen-transition metal element octahedra help explain many of these phenomena. Another key player is the orbital degree of freedom of the d-ion. It may lead to a quantum entanglement of the materials electronic wavefunctions which promotes topological states in low dimensional geometries. In this report we present a study of select topological properties at surfaces or heterostructure interfaces of a subset of these perovskites when the orientation of the structure is along the (001) or (111) direction. In contrast to the extensively studied classes of topological insulators, topology in these systems is a characteristic property of the conducting regime, thus endowing the compounds with potential spintronic and quantum computing functionalities. We conclude this communication with a personal tribute to Gérard Toulouse (in French).